Proactiveness, Stakeholder–Firm Power Difference, and Product Safety and Quality of Chinese SMEs. (26th March 2013) - Tang, Jintong; Tang, Zhi; Katz, Jerome A.
<x xml:space="preserve">Abstract</x> Despite an abundance of research on entrepreneurial orientation and various dimensions of firm financial performance, very little is known about the specific influence of proactiveness on performance. In the current research, we explore the role of proactiveness in firms' interaction with the external environment. In particular, we examine the influence of proactiveness in stakeholder–firm power difference. Further, we investigate the extent to which stakeholder–firm power difference affects product safety and quality. Using a sample of 144 Chinese small‐ and medium‐sized enterprises (SMEs), we found that proactiveness can decrease government– and media–firm power differences. Government–firm power difference reduces product concerns, yet media–firm power difference deteriorates the purported product strengths for Chinese SMEs.